Estudio de caso: plan del cambio de empaque de la marca Konzil en la gestión de ventas del canal tradicional en Lima - Kourniatis Hornung, Thalia (2018)
Henkel is a German company that operates worldwide with its three business units: adhesives, laundry & home care and beauty care. In this last category they have Konzil as a brand within their portfolio. The case will expose Konzil packaging change process for the sales management of the traditional channel in Lima. The problem that arises is the modification of the packaging of the product, which was part of a regional strategy change during 2017, which was detrimental to the sales of the brand. Some actions that the company adopted were a re-launch of the product with a new packaging for the consumer, which has the same content for both shampoo and conditioner (25ml each sachet), as well as a new package for the channel: hangers that came with two strips of sachets each, one of shampoo and another conditioner. Previously, in the hangers came only conditioner (24 sachets) and the shampoo was sold in display (40 sachets each). Part of the strategy was to have the same packaging for shampoo and conditioner to promote the placement of a greater consumption of shampoo in the points of sale. However, no client-oriented action was generated. This generated annoyance in the retailers, who were forced to buy the same quantity of shampoo, that was not the product that rotated the most. This was transferred to all the channels, negatively impacting sales because the distributor no longer wanted to continue buying a product that generated high inventories. Given this, solutions are proposed from the operational marketing and sales management aimed at achieving the company's goal: increase the market share of shampoo in the Peruvian market, considering that in Peru the penetration of shampoo category is up to 5 times larger than conditioner. During the development of this case, you can briefly read the history of Konzil since its inception in Peru in order to understand the strong positioning of the brand associated with the conditioner known as "Rinse". To conclude, the packaging change was not the best decision to increase the market share of shampoo because the strategy was more focused on the sell in than on the sell out, in other words, the strategy was more focused on the channels rather than the consumer. In this situation, it is recommended to have a vision not only regional, but also local, taking into consideration prior market research before relaunching a product. Likewise, have comprehensive plans that allow the movement of inventories to be generated from the sell out and this together with a reinforcement in the sales fundamentals such as the success photo, visibility in point of sale, training of the commercial team, commitment and attitude of the team.